The links between internationalization, skills and wages: The role of differences across firms and across partner countries - Francesco Serti; Chiara Tomasi; Antonello Zanfei (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
Using firm level data on Italian manufacturing industry, we examine how trade activities are related to workforce composition and wages. We contribute to empirical research on these issues in three ways. First, we provide novel evidence that is consistent with multi-attribute models on firm heterogeneity and trade. In fact we show that even after controlling for various firm characteristics, including size and capital intensity, exporters still pay higher wages and employ more skilled workers than non exporters. Second, we consider the engagement of firms in international transactions, either by means of exports, imports or a combination of the two. We show that failing to control for the importing activities may bias upward export premia. Third, we look at how the wage and the employment structures of trading firms change with the country of destination and origin of trade flows. We find that wage and skill premia increase for both exporters and importers as they trade with more distant markets. Richer countries are instead associated with higher premia for importers and not for exporters.
Keywords: F10; F16; J21; 330; heterogeneous firms; exports; imports; wage; skills; market heterogeneity